Does a 'direct' transfer protocol reduce time to coronary angiography for patients with non-ST-elevation acute coronary syndromes? A prospective observational study. Issue 9 (29th September 2014) - Gallagher, S M; Lovell, M J; Jones, D A; Ferguson, E; Ahktar, A; Buckhoree, Z; Wragg, A; Knight, C J; Mathur, A; Smith, E J; Cliffe, S; Archbold, R A; et al.
Abstract : Objective: National guidelines recommend 'early' coronary angiography within 96 h of presentation for patients with non-ST elevation acute coronary syndromes (NSTE-ACS). Most patients with NSTE-ACS present to their district general hospital (DGH), and await transfer to the regional cardiac centre for angiography. This care model has inherent time delays, and delivery of timely angiography is problematic. The objective of this study was to assess a novel clinical care pathway for the management of NSTE-ACS, known locally as the Heart Attack Centre-Extension or HAC-X, designed to rapidly identify patients with NSTE-ACS while in DGH emergency departments (ED) and facilitate transfer to the regional interventional centre for 'early' coronary angiography. Methods: This was an observational study of 702 patients divided into two groups; 391 patients treated before the instigation of the HAC-X pathway (Pre-HAC-X), and 311 patients treated via the novel pathway (Post-HAC-X). Our primary study end point was time from ED admission to coronary angiography. We also assessed the length of hospital stay. Results: Median time from ED admission to coronary angiography was 7.2 (IQR 5.1–10.2) days pre-HAC-X compared to 1.0 (IQR 0.7–2.0) day post-HAC-X (p<0.001). Median length of hospital stay was 3.0 (IQR 2.0–6.0) days post-HAC-X v 9.0 (IQR 6.0–14.0) days pre-HAC-X (p<0.0005). This equates to a reduction of six hospital bed days per NSTE-ACS admission. Conclusions: The introduction of this novel care pathway was associated with significant reductions in time to angiography and in total hospital bed occupancy for patients with NSTE-ACS.